PE 3: individual dual sports - Guico, Teresita M.; Pateña, Annalie De Castro; Faustino, Arnel; Maranan, Prenses Sara C.; Buhay, Jeffry B.; Aglipay, Celeste L. (Malabon City : Mutya Publishing House, 2023)
"Both individual and team sports seek to grow and enhance physical prowess. It includes the essential strategies people employ to compete and pay attention to their own performances. Through skill building, physical training drills, game play, and independent or self-directed physical activity, fitness levels will be raised. In order to monitor progress and make sure that nutritional and fitness goals are met, one's level of fitness, degree of physical activity, and eating habits are also evaluated. Individual sports help students build stronger bones and improve their performance in team or dual sports. Competitive sports enhance fundamental abilities while tracking advancement towards fitness and nutrition goals."
Includes references.
English.
Keywords: Individual sports; Dual sports; Physical education